2020
DOI: 10.1002/1873-3468.13897
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of the outer membrane protein OmpX by protealysin regulates Serratia proteamaculans invasion

Abstract: Protealysin is a thermolysin-like protease of Serratia proteamaculans capable of specifically cleaving actin, which correlates with the invasive activity of these bacteria. Here, we show that inactivation of the protealysin gene does not inhibit invasion but, in contrast, leads to a twofold increase in the S. proteamaculans invasive activity. By mass spectrometry, we identified the outer membrane protein OmpX as a substrate of protealysin. Recombinant E. coli carrying the OmpX gene truncated by 40 N-terminal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…Previously, we have shown that inactivation of the AHL synthase sprI gene resulted in the increase in invasive activity of S. proteamaculans preceded by the increased bacterial adhesion to the cell surface [6]. By our data, the increased adhesion of S. proteamaculans SprI(-) could be caused by both an increase in the expression of the surface protein OmpX responsible for adhesion [6][7][8] and a decrease in the activity of protease protealysin, whose substrate is OmpX [7,8]. On the other hand, the AHL signaling molecules can directly affect host cells and their multiple signaling pathways by triggering calcium mobilization, activation of Rho GTPases, MAPK, and NFκB that control diverse host cells functions and behaviors, including cytoskeleton remodeling [9].…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…Previously, we have shown that inactivation of the AHL synthase sprI gene resulted in the increase in invasive activity of S. proteamaculans preceded by the increased bacterial adhesion to the cell surface [6]. By our data, the increased adhesion of S. proteamaculans SprI(-) could be caused by both an increase in the expression of the surface protein OmpX responsible for adhesion [6][7][8] and a decrease in the activity of protease protealysin, whose substrate is OmpX [7,8]. On the other hand, the AHL signaling molecules can directly affect host cells and their multiple signaling pathways by triggering calcium mobilization, activation of Rho GTPases, MAPK, and NFκB that control diverse host cells functions and behaviors, including cytoskeleton remodeling [9].…”
Section: Introductionsupporting
confidence: 52%
“…We have shown that inactivation of the AHL synthase sprI gene led to a more than fourfold increase in the invasive activity of S. proteamaculans as a result of increased adhesion [6]. This increase in the adhesion of S. proteamaculans with inactivated AHL synthase gene can be caused by an increase in the amount of the surface protein OmpX and a decrease in the activity of the protease protealysin, the substrate of which is OmpX [6][7][8]. These results allowed us to suggest that synthesis of AHLs controls the invasion of S. proteamaculans by accumulation on the bacterial surface of full-length OmpX not cleaved by protealysin [6].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations